MODALITY IN MALAY LANGUAGE IN KAMPUNG TUA TANJUNG RIAU BATAM - Hilda Safitri; Siti Ainim Liusti (University of Kuningan, 2025)
This study aims to describe the types and functions of modality in Malay language used by the people of Kampung Tua Tanjung Riau, Batam, in daily interaction and communication. The approach used is qualitative with descriptive method. The data is in the form of community speech containing modality, obtained through free listening, recording, and note-taking techniques. Data validity was tested through triangulation, and analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that people use four types of modality, namely intensional, epistemic, deontic, and dynamic. Intentional modality is the most dominant type, especially in the meaning of volitional. In addition, three main functions of modality in community communication were found. This finding indicates that people consciously utilize modality as an important part of interaction. The conclusion of this study states that modality has a central role in the communication system of the community of Kampung Tua Tanjung Riau. Tanjung Riau Malay language has a distinctive and rich modality system, which reflects the culture and way of thinking of its speakers. This research is expected to be a contribution to the preservation and development of regional linguistic studies, as well as a reference for further research in the field of local language and culture.